Shoulder pain among type 2 diabetes mellitus patients: A cross-sectional study in Chilean population - Habechian, Fernanda A.P.; Flores-Quezada, Mauricio Esteban; Martinez-Ortega, Anais Catalina; Cuevas-Cid, Rodrigo Ignacio; Zanca, Gisele Garcia [UNESP] (Elsevier, 2025)
Aim: This study aimed determine the prevalence of shoulder pain among Chilean patients with type 2 DM and to characterize their pain intensity and associated disabilities, including an analysis of sex-based differences. Methods: A total of 151 participants with type 2 DM, aged 18–79, from family health centers in Talca, Chile, were included. Data were collected via telephone interview, capturing demographic details and information about current shoulder pain, including its duration, intensity, using a Numerical Rating Scale (NRS), and disability using the Shoulder Pain and Disability Index (SPADI). Statistical analysis was performed using frequency measures, Chi-squared tests, binary logistic regression, and Student's t-tests with SPSS version 21.0. Results: Out of 1662 eligible patients, 151 participated. The overall prevalence of shoulder pain was 53.6 % (95 % CI: 53.8–53.4), with women showing a higher prevalence (63 %; 95 % CI: 63.2–62.8) compared to men (37 %; 95 % CI: 37.2–36.8), a difference that was statistically significant (chi-square=13.5; p ≤ 0.001). The results showed that neither BMI nor sex was significantly associated with the presence of pain. No significant differences were found between sexes regarding pain intensity and disability (p ≥ 0.05). Conclusion: Shoulder pain is highly prevalent among patients with type 2 DM, with a higher prevalence in women. Future research should explore the impact of this condition on patients and develop targeted musculoskeletal rehabilitation programs.
Keywords: Diabetes mellitus; Musculoskeletal disorders; Prevalence; Shoulder pain